The New Testament Citing the New Testament in (Copies of) the New Testament: Diples and Testimony Lists in Early Manuscripts - Hill, Charles E. (TC, 2024)
This essay considers two scribal projects from antiquity that record a belief that some New Testament authors at times cited the work of other New Testament writers. The scribes of the fourth- or fifth-century pandects, Sinaiticus (01 א), Alexandrinus (A 02), Vaticanus (B 03), and Ephraemi Rescriptus (C 04), sometimes placed diples (>) in left-hand margins to mark where a New Testament writer has cited an Old Testament book. This essay identifies three New Testament passages (Acts 13:25; 1 Tim 5:18b; 2 Pet 1:17) that receive diples in one or more of the pandects and suggests that these diples denote a belief that the authors, Luke, Paul, and Peter, were reliant upon one of the New Testament gospels. The second scribal project is the μαρτύρια lists within the Euthalian Apparatus for Acts, the Catholic Epistles, and the Pauline Epistles, which record testimonies each book is believed to have taken from other sources. Here the sources are named and so are not ambiguous. The lists indicate a view that some New Testament authors cited not only Old Testament but also pagan, apocryphal, and New Testament predecessors. Seven testimonia are identified as deriving from one of the gospels (Acts 1:4–5; 13:25; 2 Pet 1:17; 2:20; 1 John 1:5; 1 Cor 11:24–25; 1 Tim 5:18b), including all three passages that receive diples in one of the pandects, each of the three being attributed to Matthew. The findings of this essay also shed further light on the origins of the Euthalian Apparatus and on the applicability of the term diplae sacrae.